PRACTICAL GUIDELINES FOR ASSESSING CORAL CALCIFICATION VIA COMPUTED TOMOGRAPHY - Nurhati, Intan Suci (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2018)
Coral calcification as the product of extension rate and skeletal density, is projected to change under marine environmental changes of local (e.g., sedimentation, eutrophication) and global (e.g., warming, ocean acidification) scales. For the regional effort to monitor the ecological impacts of ocean acidification on coral reef ecosystems, the Intergovernmental Oceanographic Commission Sub-Commission for the Western Pacific (IOC-WESTPAC) has incorporated an interdisciplinary approach that includes monitoring of seawater carbonate parameters, coral calcification, net calcification minus bioerosion, and reef community structure. Currently, there is a need to formulate a standard operating procedure (SOP) for assessing coral calcification over the recent years via coral cores. The SOP needs to yield accurate data in a cost-effective way that can be applied by researchers in the region. High variation of coral calcification parameters between coral colonies warrants a sufficiently large number of samples thus a rapid method for analyzing coral extension rate, skeletal density, and calcification. This paper outlines practical guidelines for assessing coral calcification from the field to laboratory using the three-dimensional computed tomography (CT) method.